基于道路模拟激励谱的AMT执行机构虚拟振动试验方法研究 - 邹喜红; 熊锋; 钱晓渝; 余勇; 杨真亮 (Jixie chuandong)
The vibration fatigue reliability of AMT actuator is one of the most significant performances of AMT.For acquiring the accurate and efficient analysis and evaluation of AMT actuator vibration fatigue reliability,the AMT actuator actual driving road load spectrum are collected in Dongfeng test field,combined with the developed AMT actuator multi-axes road simulation test bench,the load spectrum simulation iteration method based on remote parameter matrix control with time-frequency domain error weighting coefficients 0.5respectively succeeded in achieving accurate and efficient reproducing of AMT actuator actual driving road load spectrum and thus road simulation excitation spectrum are extracted.By using the finite element analysis soft HYPERWORKS and multi-body dynamics simulation software ADAMS,the virtual rigid-flexible coupled road simulation test platform is built with reference to the actual AMT actuator multi-axes road simulation test bench.Simulation analysis is conducted with the achieved road simulation excitation spectrum as input and the outcomes are verified by actual collected spectrum and road simulation test results,thus the virtual vibration test method for AMT actuator based on road simulation excitation spectrum is established,an effective approach and method for AMT actuator vibration fatigue reliability assessment is provided.